Exploring the Biocatalytic Potential of Fe/α‐Ketoglutarate‐Dependent Halogenases. Issue 33 (15th April 2020) - Voss, Moritz; Honda Malca, Sumire; Buller, Rebecca
Abstract: Freestanding Fe/α‐ketoglutarate‐dependent halogenases are oxidoreductases that catalyze the installation of halogen atoms into unactivated sp 3 ‐hybridized carbon centers with high stereo‐ and regioselectivity. Since their discovery in 2014, a small number of indole alkaloid and amino acid halogenases have been identified and characterized. First enzyme engineering examples suggest that the accessible substrate range of these enzymes may be expanded through the use of rational enzyme design and directed evolution. Structural investigations of non‐heme iron halogenases acting on freestanding as well as tethered substrates are beginning to inform about the principles of the underlying halogenation mechanism. Abstract : Fe/α‐ketoglutarate halogenases are turning into valuable tools for the stereoselective incorporation of halogen atoms into unactivated C−H bonds. To date, halogenases which selectively derivatize free amino acids or indole alkaloids have been discovered. While first enzyme engineering examples highlight that the substrate scope can be expanded, structural and biochemical characterizations continue to inform about the enzymes' catalytic mechanism.